Thoraco-laparoscopic management of diaphragmatic hernia of adults: a case series - Chauhan, Siddharth S.; Mishra, Ajit; Dave, Sandeep; Naqvi, Jawwad; Tamaskar, Siddharth; Sharma, Vikram; Niwas, Nitin (International Surgery Journal, 2020)
Diaphragmatic hernia (DH) usually occurs in childhood; however, in adult it is uncommon. Most common aetiology of DH in adult is trauma while spontaneous DH is a rare entity accounting for <1%. The management is primarily surgical repair in the form of open or laparoscopic approach; the later has been associated with low morbidity, mortality and excellent long term outcomes with low rate of recurrence. In this case series, confirmation of the diagnosis was done by CT scan and by laparoscopy in all the patients; laparoscopic repair was performed in all the patients along with thoracoscopic aid in two cases. We found that minimal access techniques can be safely done in DH; in conditions when the herniated content are difficult to get reduced laparoscopically alone, a simultaneous thoracoscopy has helped in great deal in reducing the content and completing the procedure entirely by minimal access techniques. This gives all the advantages of minimally invasive approach like less postoperative pain, shorter hospital stay, quicker recovery and low recurrence rate; provided tissue repair is done in tension free manner by an experienced laparoscopic surgeon.